INVESTIGATING THE CONTRIBUTORY ROLE OF COMPUTER-BASED TEST ON EXAM ANXIETY IN TERTIARY EDUCATION IN EBONYI STATE, NIGERIA (IJOVTECH, 2026)
Using computer-based tests for testing is currently trending in Nigeria's educational setting. Research has linked the phenomenon to increased test anxiety among students. The present study examined the difference between students in public and private tertiary institutions on CBT-induced test anxiety. Two hundred students pooled from public and private tertiary institutions participated in the study. Data for the research was collected using a self-report measure. The findings affirmed the prevalence of test anxiety occasioned by CBT. The t-test analysis conducted on the data revealed no statistically significant difference between public and private CBT-induced test anxiety. The findings and recommendations are discussed.